1969
DOI: 10.2307/1933885
|View full text |Cite
|
Sign up to set email alerts
|

Light Control of Aquatic Insect Activity and Drift

Abstract: Investigations on aquatic insect activity, measured as drift in an artificial stream system with rigid light and temperature conditions, demonstrated a light—controlled, labile, exogenously—mediated activity rhythm. A threshold value for light, incident at the water surface, which when decreased led to high drift rates, and when increased suppressed activity, was determined to lie between 10—3 and 10—4 ft—c (10—2 and 10—3 lux). Preliminary experiments showed variations in wavelength to have little effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 28 publications
(19 reference statements)
2
46
0
1
Order By: Relevance
“…For instance, given the conflicting demands on benthic invertebrates to maximize foraging intake and minimize predation risk (Gilliam and Fraser 1987;Lima and Dill 1990), active drift is likely a joint response to both predation risk and local per capita resource availability. This trade-off between maximizing energy intake and minimizing mortality is exemplified by strong nocturnal peaks in drift (Bishop 1969), which are usually attributed to invertebrates searching for new foraging patches while avoiding predation from visually foraging, drift-feeding fishes (Allan 1978;Flecker 1992). In this case, invertebrates drift at night to minimize predation risk from drift-feeding fishes, but the ultimate motivation for moving among habitats is likely resource limitation, although escape from nocturnally foraging benthic predators may also play a role (Hammock et al 2012).…”
Section: Drift Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, given the conflicting demands on benthic invertebrates to maximize foraging intake and minimize predation risk (Gilliam and Fraser 1987;Lima and Dill 1990), active drift is likely a joint response to both predation risk and local per capita resource availability. This trade-off between maximizing energy intake and minimizing mortality is exemplified by strong nocturnal peaks in drift (Bishop 1969), which are usually attributed to invertebrates searching for new foraging patches while avoiding predation from visually foraging, drift-feeding fishes (Allan 1978;Flecker 1992). In this case, invertebrates drift at night to minimize predation risk from drift-feeding fishes, but the ultimate motivation for moving among habitats is likely resource limitation, although escape from nocturnally foraging benthic predators may also play a role (Hammock et al 2012).…”
Section: Drift Entrymentioning
confidence: 99%
“…Leung et al (2009) used a simple bioenergetics approach to estimate drift consumption by young-of-the-year and 1-year-old cutthroat trout feeding in pools at 25% and 50% of their maximum daily consumption and concluded that 36%-71% of drift could be lost to fish predation in a small trout stream. While these estimates suggest predation on drift may be a large component of daytime drift depletion, foraging efficiency and activity are generally much lower at night (Allan 1978;Sagar and Glova 1988; but see Elliott 2011) when drift abundances generally peak in fish-bearing streams (Bishop 1969). Therefore, while fish may deplete a major portion of diurnal drift in smaller streams, overall losses due to predation may be a negligible fraction of the total drift flux.…”
Section: Drift Exitmentioning
confidence: 99%
“…It has become clear that ALAN can affect the movement, reproduction, physiology and behaviour of animals (Longcore and Rich, 2004;Navara and Nelson, 2007;Perkin et al, 2011;Kurvers and Hölker, 2015;Honnen et al, 2016). Changes to animal movement have been reported in freshwater ecosystems, where ALAN can disrupt the diel vertical migration of zooplankton, arthropod drift (Bishop, 1969;Moore et al, 2001;Perkin et al, 2014b), and fish predation (Tabor et al, 2004). The attraction of terrestrial insects to ALAN light sources is well-documented (Eisenbeis et al, 2006) and it can have negative consequences (Horváth et al, 2009;Perkin et al, 2014a;Degen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, light intensity and wavelength are known to influence biological and physiological processes in insects (Bishop 1969;Manuwoto and Scriber 1985;Sakai et al 2002). Predators and parasitoids have received substantial attention in this regard because of the need to understand photic influences on biological control outcomes (e.g., Omkar et al 2005;Malaquias et al 2010) and the suitability of lighting regimes for mass rearing natural enemies for augmentative biological control applications (Chambers 1977).…”
Section: Introductionmentioning
confidence: 99%